SEGMENTAL ERRORS INDICATED BY FORMANTS: A PRAAT ANALYSIS - Ade Namira; Rahmadsyah Rangkuti (Hikari: Jurnal Bahasa dan Kebudayaan, 2022)
This study aims to find out the segmental error occurred by English students by concerning to their formants. This study used descriptive qualitative method. The subjects were a native speaker whose sound was taken from GStatic and two students whose background were Javanese and majoring English Education Study Program. The data were in the form sound and formants gotten from PRAAT software after input the sounds. The data were analyzed, described, and concluded. The result showed that the segmental error faced by the participants were /?/, /?/, /e/, /?/, and /?/. Participants’ formants tended to higher or lower than Native speaker’s formants.